Tourist Attractiveness of the Saratov Region (Based on Empirical Research) - Dmitry Valerievich Akaev; Aleksandr Aleksandrovich Shugaev (Управленческое консультирование)
The article discusses approaches to the study of tourist attractiveness in terms of economics, marketing, social communication and sociology of management. The results of the authorial sociological study of citizens’ overall satisfaction with the quality of tourist services and tourist attractiveness of the Saratov Region are analyzed. A questionnaire survey of 1,200 respondents was conducted in the autumn of 2016, and the results formed the basis for the implementation of the project «Introduction to the Saratov Region: A Guide to Historical Sites», supported by a Presidential grant from NGO. The conclusion is that domestic tourism in the Saratov Region is now in the stage of development and determining its place among the potential visitors. As it is impossible to compete with foreign beach, mountain, and shopping routes for objective geographical, climatic and economic reasons, it is necessary to look for opportunities in other equally promising directions.